Scientific and Technical overview about Artificial Proprioception in Prosthetics - Diaz-Hernandez, Octavio (Revista Mexicana de Ingenieria Biomedica, 2025)
Proprioception is the body's ability to perceive its position and movement, which plays a crucial role in motor control, and its loss following amputation presents significant challenges for prosthesis users. Artificial Proprioception is an innovation that enhances sensory feedback and motor control in prosthetic devices. This review presents a comprehensive overview of current research and technological developments in Artificial Proprioception, focusing on sensory feedback mechanisms, neural interface systems, and the integration of biomechatronic technologies. With a growing interest in restoring sensory feedback for amputees, this work explores key innovations such as electrotactile and vibrotactile stimulation, artificial intelligence, and neural interfaces that enable a more natural and intuitive prosthetic control. The methodology included reviewing studies from databases like Scopus, Web of Science, and PubMed on proprioceptive feedback in prosthetics in recent years. It evaluates research related to sensory feedback, amputation levels, neural interfaces, and technological advancements, classifying papers by feedback mechanisms. The paper concludes by discussing potential future developments, including more advanced, user-centered prosthetic devices that address the sensory needs of amputees and improve their quality of life.